Bulk heterojunction blend (NiPcTs:PEDOT:PSS) in gas sensing - Abood, Morooj A. (Iraqi Journal of Physics, 2019)
Thin films of bulk heterojunction blend Ni-Phthalocyanine Tetrasulfonic acid tetrasodium salt and dpoly (3, 4-ethylenedioxythiophene) poly (styrenesulfonate) (NiPcTs: PEDOT: PSS) with different (PEDOT:PSS) concentrations (0.5, 1, 2) are prepared using spin coating technique with thickness 100 nm on glass and Si substrate. The X-Ray diffraction pattern of NiPcTs powder was studied and compared with NiPc powder, the pattern showed that the structure is a polycrystalline with monoclinic phase. XRD analysis of as-deposited (NiPcTs/PEDOT:PSS) thin films blends in dicated that the film appeared at(100), (102) in concentrations (0.5, 1) and (100) in concentration (2). The grain size is increased with increasing (PEDOT:PSS) concentrations. FTIR measurements for these bulk heterojunction blend thin films also carried out in this work and gave good information about the bonds and their locations. Sensor measurements of Si/NiPcTS:PEDOT:PSS bulk heterojunctions blend thin films show a good sensitivity for NO2 gas Compared to NH3gas. The NiPcTS/PEDOT:PSS gas sensor device work at room temperature than high temperature for NO2 gas but good sensitivity at100ºC for NH3 gas and sensor work more effectively in 0.5 concentration for both gases.